Modelagem e otimização de redes de filas finitas - Helgem de Souza Ribeiro Martins (2016)
The joint buer and server optimization problem (BCAP) is a non-linear optimization problem with integer decision variables that optimizes the number of buers and servers such that the resulting throughput is greater than a pre-dened threshold throughput. This work presents a detailed review of the current literature that deals with allocation problems, especially the BCAP, and a quite eective methodology in solving this problem, which consists in a combination of approximate methods and Powell algorithm, a derivative-free optimization algorithm. The methodology was applied to networks of queues in series, split, and merge basic topologies, producing very encouraging results that pointed at robust and homogeneous solutions.